2020
DOI: 10.1002/jdd.12173
|View full text |Cite
|
Sign up to set email alerts
|

Dental anxiety in adult patients treated by dental students: A systematic review

Abstract: Purpose/objectives Dental anxiety is common and can propagate a vicious cycle of dental neglect and anxiety‐provoking treatment. Patient, procedural, and operator factors are important contributions. This review aims to explore risk factors for dental anxiety in adult patients treated by dental students, in order to improve awareness of relevant factors and aid patient management. Methods Systematic searching of PubMed and Scopus databases was performed. Inclusion criteria were: studies assessing at least 1 ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Females presented with a higher mean MDAS both pre and posttreatment compared with males. This finding is similar to other previous studies [2,5,17,21]. Those patients with unpleasant, unsatisfied and unhappy previous dental experience showed significant difference in comparison to those who experienced comfortable or interesting previous dental experience.…”
Section: Discussionsupporting
confidence: 91%
“…Females presented with a higher mean MDAS both pre and posttreatment compared with males. This finding is similar to other previous studies [2,5,17,21]. Those patients with unpleasant, unsatisfied and unhappy previous dental experience showed significant difference in comparison to those who experienced comfortable or interesting previous dental experience.…”
Section: Discussionsupporting
confidence: 91%
“…Before coming to the office, the parents have to prepare the child for treatment by following the advice of the dentist. In this way—with parental preparation at home and the application of methods of shaping behavior in the office—the child is gradually prepared for any planned procedure without the development of dental fear and anxiety [ 10 , 35 ]. With this research, we have shown that dental anxiety is high in the area of southeast Europe.…”
Section: Discussionmentioning
confidence: 99%
“…If anxiety is not diagnosed in time, a “vicious circle of dental anxiety” occurs. Dental fear and anxiety lead to the neglect of oral health, resulting in a worsening of the problem, and this leads to longer and more painful treatment that increases fear in the patient and leads to re-avoidance of the office and the entire dental team [ 9 , 10 ]. In a study by Mueller et al [ 11 ] from 2022, dental anxiety and negative dental experiences significantly reduced the participants’ perception of dental self-efficacy, as well as dental self-examination.…”
Section: Introductionmentioning
confidence: 99%
“…28 Another investigation by Gosh et al indicated this by showing that dental neglect was strongly significantly associated with dental anxiety. 29 Reduced interest in adequately taking care of their children's teeth, by reduced follow up for periodontal and restorative management modalities, was also significantly associated with the practice of parenteral neglect and reduced compliance to their dental treatment plans. 30 Among studies in the literature, some had reported that these parents were characterized by frequent exposure to emergency pain-relieving modalities, reduced show-up at dental clinics, decreased interest in alleviating their dental education and reduced oral hygiene self-practices.…”
Section: Etiologymentioning
confidence: 99%